2015
DOI: 10.1371/journal.pone.0125573
|View full text |Cite
|
Sign up to set email alerts
|

Gap Effect Abnormalities during a Visually Guided Pro-Saccade Task in Children with Attention Deficit Hyperactivity Disorder

Abstract: Attention deficit hyperactivity disorder (ADHD) is a neurodevelopmental disorder that starts in early childhood and has a comprehensive impact on psychosocial activity and education as well as general health across the lifespan. Despite its prevalence, the current diagnostic criteria for ADHD are debated. Saccadic eye movements are easy to quantify and may be a quantitative biomarker for a wide variety of neurological and psychiatric disorders, including ADHD. The goal of this study was to examine whether chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 60 publications
2
19
0
Order By: Relevance
“…Indeed, this effect has been reported in a number of previous studies (e.g. [11,14,55,56].). Importantly, however, our results add novelty to these findings by showing that phasic alerting cues normalized this visual attention pattern by decreasing saccadic latencies in the ADHD group, but this effect was not observed in typically developing children.…”
Section: Discussionsupporting
confidence: 72%
“…Indeed, this effect has been reported in a number of previous studies (e.g. [11,14,55,56].). Importantly, however, our results add novelty to these findings by showing that phasic alerting cues normalized this visual attention pattern by decreasing saccadic latencies in the ADHD group, but this effect was not observed in typically developing children.…”
Section: Discussionsupporting
confidence: 72%
“…In other words, if gazing at the target is steadier, saccade delay occurs. It has been found that the saccade latency of children with attention deficit hyperactivity disorder (ADHD) is slower than typically developing children [18]. In addition, it is anticipated that the motion of saccades is influenced from not only the superior colliculus but also the central nervous system affecting the CFF [19].…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the difficulty of performing actions in the antisaccadic tasks persisted in adulthood, with the most relevant problem observed in adequate preparation, but not in the motor task. 39 Matsuo et al 40 analysed visual, neurological or psychiatric primary results using samples of children with a maximum age of 11 years. The authors used an eye-tracker to characterise the eye movements.…”
Section: Adhd Studiesmentioning
confidence: 99%
“…The authors did not include any measurement of the status of the visual health or the binocular vision that could cause bias when analysing the results. Only Matsuo et al 40 considered optical correction but did not analyse the status of the binocular vision. It should be considered that a great variety of studies have shown how refractive error, accommodation and binocular vision dysfunctions can affect reading and learning.…”
Section: Dcd Studymentioning
confidence: 99%